GENEALOGI DAN PENYEBARAN THARIQAH QADIRIYAH WA NAQSHABANDIYAH DI JAWA - Aly Mashar (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2016)
This article investigates the geneology and spread of Thariqah Qadiriyah wa Naqshabandiyah in Java. Based on the previous literatures (Dhofier, Martin van Bruinessen, Zulkifli, and Mulyati), it was found out that in Java the genealogy of the thariqah formed by Syekh Ahmad Khatib Sambas directed to the three primary khalifah, i.e. Syekh Abdul Karim Banten, Syekh Ahmad Thalhah Cirebon, and Syekh Muhammad Hasbullah Madura, then spread out across Java Island through the four centers (on 1970s), such as Suryalaya, Rejoso, Mranggen, and Pangentongan. However, the writer found out that there were four khalifahs, including Syekhona Kholil Bangkalan Madura; with the nine dissemination centers (in 1970s) including Berjan Purworejo, Sawah Pulo Surabaya, Cukir Jombang, Kencong Kediri, and Dawe Kudus.